Knowledge level of improved dairy husbandry practices in tribal areas of Southern Gujarat (Indian Journal of Animal Production and Management, 2024)
The present study was conducted in the Valsad district of Southern Gujarat to assess the knowledge level of randomly selected 240 dairy farmers about improved dairy husbandry practices. The analysis of data collected by personal interview method revealed that majority of dairy farmers had medium knowledge level on different aspects of improved dairy husbandry practices viz. 58.78% for feeding, 80.00% for breeding, 60.00% for general management and 69.58% for healthcare. The overall knowledge levels of the respondents in improved dairy husbandry practices fall under low, medium and high categories are 17.08%, 63.34% and 19.58%, respectively. The knowledge index of different aspect of improved dairy husbandry practices of feeding, breeding, general management and health care were 52.03, 76.72, 45.57 and 69.11%, respectively and overall knowledge index of improved dairy husbandry practices was 60.86% which indicated medium knowledge level of dairy farmers in the study area.
Keywords: Dairy Husbandry; Knowledge; Practices; Tribal areas